The Effectiveness of Codesters in Teaching Basic Computer Science Topics - (:unkn) unknown (My University, 2019)
Founded in 2014, Codesters is a visual programming environment (VPE) like the popular Scratch and Alice. Its goal is to teach middle school and older student’s computer programming. Unlike its predecessors, users of Codesters drag and drop actual Python code instead of blocks and can edit the code themselves. Codesters has also developed modules that integrate coding lessons into the VPE. In this study, we consider the Codesters Python 1 module and investigate its effectiveness in teaching the basic coding concepts of variables, loops and conditionals. During Fall 2018 and Spring 2019, we ran a coding class for eighth graders at a local Milwaukee school based on this module. We gave a pre-test, three quizzes and a post-test to evaluate what the students have learned. We then analyzed the results of these evaluations and compared them to those taken by students who learned programming in a traditional CS1 class. Our results indicate that users of Codesters understood loops and conditionals as well as the students from the traditional CS1 class. We also found that the pre-test was a poor indicator of students’ performance in the coding class suggesting that Codesters is able to engage students who might not necessarily excel in a traditional classroom.
Keywords: Block Programming; Codesters; K-12 Education; Visual Programming Environments; Visual Programming Languages